WORKPLACE SPIRITUALITY AND WORK ENGAGEMENT AMONG HIGH SCHOOL TEACHERS IN BANDA ACEH - Aprilia, Eka Dian; Katiara, Oshan (Faculty of Psychology, Diponegoro University, 2020)
Work engagement is vivacious for teachers to improve and maintain the quality of education. One of the factors that can improve work engagement is workplace spirituality. The study aimed to determine the relationship between workplace spirituality and work engagement of High School teachers. This study used a quantitative method with a cluster random sampling technique and the sample size was based on Isaac and Michael table with a 5% error level with 120 participants who work as civil servant High School teachers in Banda Aceh. The scales used in this study are an adaptation of Workplace Spirituality Scale developed by Milliman, Czaplewski, and Ferguson and adaptation of Utrecht Work Engagement Scale (UWES) by Schaufeli, Salanova, GonzalezRoma, and Bakker. The result of data analysis using the Pearson Product-Moment Correlation test showed a correlation coefficient of .397 with p-value = .000 (p < .05). The hypothesis was confirmed so it can be concluded that there was a significant positive correlation between workplace spirituality and work engagement of High School teachers. It means the higher the workplace spirituality of teachers, the higher the work engagement of teacher will be and vice versa. The results showed that the majority of workplace spirituality and work engagement of High School teachers in Banda Aceh classified into â€œhighâ€ category.